1996
DOI: 10.1093/jmedent/33.2.195
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Volatiles from Neem and Other Natural Products on Gonotrophic Cycle and Oviposition of Anopheles stephensi and An. culicifacies (Diptera: Culicidae)

Abstract: The gonotrophic cycle of female Anopheles was impaired by exposure to volatiles of neem, (Azadirachta indica), reetha, (Sapindus mukorossi), and garlic, (Allium sativum), but not to castor seeds and cotton seed oil. A brief exposure to contact or volatile extracts from neem suppressed rather than inhibited oviposition. Complete inhibition of oviposition was observed by exposure of mosquitoes to neem oil and 1 fraction containing volatile components. Vitellogenesis was impaired irreversably by long-term exposur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(45 citation statements)
references
References 0 publications
3
42
0
Order By: Relevance
“…This phenomenon is in agreement with previously reported decreases in oviposition for insects treated with neem products (Musabyimana et al 2001;Bruce et al 2004). Large alterations in the fecundity of insects exposed to neem have been extensively reported, such as those in the fly, C. capitata (Steffens and Schmutterer 1982); banana root borer, Cosmopolites sordidus (Germar) (Musabyimana et al 2001); and mosquitoes, A. stephensi and A. culicifacies (Dhar et al 1996). The work published by Khan et al (2007) microscopically demonstrated that the decrease in fecundity of B. cucurbitae and B. dorsalis exposed to neem compound was due to the block of ovarian development.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This phenomenon is in agreement with previously reported decreases in oviposition for insects treated with neem products (Musabyimana et al 2001;Bruce et al 2004). Large alterations in the fecundity of insects exposed to neem have been extensively reported, such as those in the fly, C. capitata (Steffens and Schmutterer 1982); banana root borer, Cosmopolites sordidus (Germar) (Musabyimana et al 2001); and mosquitoes, A. stephensi and A. culicifacies (Dhar et al 1996). The work published by Khan et al (2007) microscopically demonstrated that the decrease in fecundity of B. cucurbitae and B. dorsalis exposed to neem compound was due to the block of ovarian development.…”
Section: Discussionsupporting
confidence: 92%
“…As discussed by Weathersbee III and Tang (2002), the disruption of reproductive capability could lead to substantial population decline over time. Furthermore, Dhar et al (1996) revealed that exposure to neem extract suppressed rather than inhibited oviposition in mosquitoes. This might, in part, explain our result that flies in the third generation showed normal bioavailability after exposure to neem.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The constituents of plants volatiles could enter test insects either through the cuticle or the spiracle [29]. The probable reason for the death of insects when exposed to volatiles compounds could be either due to interference in gaseous exchange in respiration or asphyxiation [30].…”
Section: Chemical Constituentsmentioning
confidence: 99%
“…They also tend to be safe for animals and the environment [12]. Specifically, many studies have drawn attention to the toxic effects of plant extracts on related Diptera [8,13,14].…”
Section: Introductionmentioning
confidence: 99%